Assessment of hemodialysis adequacy and associated factors related to hemodialysis adequacy in end - stage renal disease patients - Watcharananan, Yingluk (Journal of Medical and Public Health Region 4, 2024)
Patients with end stage renal disease receiving hemodialysis have increased risk of morbidity and mortality from inadequate hemodialysis. This study aims to access the adequacy of hemodialysis and to study factors related to hemodialysis adequacy in patients with end stage renal disease. This study was performed as a retrospective cohort study in end stage renal disease patients undergoing hemodialysis at 2 hemodialysis centers in Langsuan between 1 July and 30 September 2022. Data were analyzed to access adequacy and associated factors related to hemodialysis adequacy using multivariate logistic regression analysis. One hundred and eighty patients were enrolled in the study. Patients achieved hemodialysis adequacy for 76% of Kt/V and 77% of URR, mean Kt/V 1.73 ± 0.53 and mean URR 73.28 ± 12.36.There were four factors significantly related to adequacy of hemodialysis: female adjust OR = 4.41, 95% CI 1.89 – 10.28, p = 0.001, dialyzer surface area of 2.1m2 adjust OR = 3.32, 95% CI 1.28 - 8.59, p = 0.013, blood flow rate 350 ml/min adjust OR = 4.39, 95% CI 1.79 - 10.76, p = 0.001, dialysis frequency 3 times per week adjust OR = 4.32, 95% CI 1.71 - 10.93, p = 0.002. There were four factors significantly related to hemodialysis adequacy including female, dialyzer surface area of 2.1m2, blood flow rate 350 ml/min, dialysis frequency 3 times per week